Perancangan Aplikasi Pemesanan Berbasis Web Pada Café “Bullax Saung” Jember - Mike Wahyuningtyas (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This research was conducted to design a web-based ordering system at Bullax Saung Café as a solution to various problems that arise in the manual ordering process, such as recording errors, late order delivery, and difficulty in recapitulating transactions. The research used a Waterfall approach with stages of observation, interviews, literature studies, needs analysis, and system design. System modeling was carried out using Unified Modeling Language (UML) including use case diagrams, activity diagrams, and database design using Entity Relationship Diagrams (ERD). The interface design was made based on the User Centered Design approach for ease of use. The findings indicate that the manual system has a high error rate and an inefficient workflow, so the digital system is more capable of supporting café operations. The resulting system design can be a solution to the operational problems of Bullax Saung Café and is able to increase the effectiveness of the ordering process.